The urban security project - Roberto Bolici; Matteo Gambaro (Agathón)
This essay aims to critically re-read the birth and evolution of design methodologies aimed at improving safety conditions and quality of life in cities. In particular, referring to the American cultural context and the birth of the CPTED (Crime Prevention Through Environmental Design) – that first experienced the environmental approach to urban safety – three recent French experiences are analyzed from the urban scale to that of the building artefact and the Italian reality takes stock, also in the light of the recent Legislative Decree of 2017 and the 2010 UNI Standard that punctually outlines an articulated design approach, in fact inapplicable.